Exploring the relationship between technology adaptation and digital innovation with leadership strategies as a mediator for digital leadership in the underprivileged school - Robit Bin Yusie Fus Han; Abdul Said Bin Ambotang; Ghazali@Hassan Bin Sulaiman; Syahrul Nizam Salam; Darussalam Nehemia Bonel Pantulusang (Human Resource Management Academic Research Society, 2025)
This study aims to understand the relationship between technology adaptation, digital innovation, leadership strategy, and digital leadership in the context of digital transformation. The study involved 175 headmasters from schools in Sabah, using the PLS-SEM (Partial Least Squares Structural Equation Modeling) approach through Smart PLS 4 software. This approach was chosen because it is suitable for models with latent variables and moderate sample sizes. Data analysis involves three main steps: (a) Reliability and Validity Tests to ensure internal validity of constructs, (b) Measurement Model Analysis to examine the relationship between leadership strategies, emotional intelligence, and digital leadership, and (c) Relationship Validation Tests to validate significant relationships through path coefficients and p-values.The findings show that leadership strategy plays an important role as an intermediary element between the adaptation of technology and digital innovation to digital leadership. While technology and innovation provide an important foundation, their impact depends on a carefully planned strategy. The significant relationship between leadership strategy and digital leadership shows that smart leaders leveraging strategies can drive adoption of technology and accelerate organizational culture transformation. However, the direct link between technology adoption and digital leadership is insignificant, suggesting the need for work culture change and leadership capacity building. This study makes an important contribution to the literature on digital transformation, emphasizing the need for a holistic approach that combines modern technology, innovative strategies, and a progressive organizational culture. The decision also provides guidance for organizational leaders to increase the effectiveness of digital transformation through appropriate leadership strategies and strengthening leadership capacity.